2004
DOI: 10.1038/sj.ejhg.5201313
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype structure of the beta adrenergic receptor genes in US Caucasians and African Americans

Abstract: The beta-adrenergic receptors (beta-AR) are G protein-coupled receptors activated by epinephrine and norepinephrine and are involved in a variety of their physiological functions. Previously, three beta-AR genes (ADRB1, ADRB2 and ADRB3) were resequenced, identifying polymorphisms that were used in genetic association studies of cardiovascular and metabolic disorders. These studies have produced intriguing but inconsistent results, potentially because the known functional variants: ADRB1 Arg389Gly and Gly49Ser,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 39 publications
(25 reference statements)
6
33
0
Order By: Relevance
“…The observed allele and haplotype frequencies differed by ethnicity and were comparable to those for the general US population. 13 We observed no association between the 4 SNPs and odds of SCD for cases compared to both control groups for all 4 genetic models. Odds ratios for SCD for Case vs. CAD Control and Case vs. Non-CAD Control comparisons for the dominant and recessive models are presented in Figure 1.…”
Section: Ucsf Scd Case-control Studymentioning
confidence: 61%
See 2 more Smart Citations
“…The observed allele and haplotype frequencies differed by ethnicity and were comparable to those for the general US population. 13 We observed no association between the 4 SNPs and odds of SCD for cases compared to both control groups for all 4 genetic models. Odds ratios for SCD for Case vs. CAD Control and Case vs. Non-CAD Control comparisons for the dominant and recessive models are presented in Figure 1.…”
Section: Ucsf Scd Case-control Studymentioning
confidence: 61%
“…The observed allele and haplotype frequencies differed by ethnicity, and were similar to those obtained in the SCD Case Control study and previous reports. 13,18 Risk for the outcomes of SCD, SCD + NFVA, and all-cause mortality, were examined for each SNP under the 4 genetic models. The risks for SCD, SCD + NFVA, and all-cause mortality as assessed by the dominant and recessive models for all SNPs tested are shown in Figure 2.…”
Section: Hers Cohort Scd Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This is very likely due to the linkage disequilibrium between A46G and C79G. [38][39][40] Owing to linkage disequilibrium, subjects homozygous for G79 are nearly always homozygous for G46, whereas naturally occurring A46/G79 is rare. [41][42][43] Pojoga et al 6 observed that AA46/ CC79 was significantly associated with higher blood pressure, which might be attributed to the enhancement of the AA46/CC79 diplotype.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] Both polymorphisms showed Hardy-Weinberg proportions among the founders. Haplotype frequencies among founders are given in Table 2, and indicate high LD between these polymorphisms (D 0 = 0.99; P-value < 0.0001; r 2 = 0.42).…”
Section: Resultsmentioning
confidence: 91%